2023
DOI: 10.1111/phen.12403
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent changes in reproductive allocation in a facultative ectoparasite, the blowfly Lucilia sericata (Meigen) (Calliphoridae)

Abstract: Organisms trade‐off limited resources between life‐history traits to maximize fitness. In particular, costs associated with reproduction are balanced against somatic maintenance and this can result in age‐dependent changes in the optimal allocation of resource to reproduction. Changes in the allocation of resources to reproduction with age were considered in the facultatively parasitic blowfly Lucilia sericata (Diptera: Calliphoridae), using biochemical analysis of lipids in the body and ovary, and lipid and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Through oosorption, females are able to reallocate reproductive resources (mostly yolk material from mature oocytes) to fuel somatic maintenance, which would otherwise be wasted as unfertilised eggs. Thus, in response to a mating delay, females may allocate less resources to egg production and more to somatic maintenance, expecting future mating chances and reproduction (Alqurashi et al, 2023; Fadamiro & Baker, 1999; Proshold et al, 1982; Zheng et al, 2020). Our results, however, suggest that oosorption appears to be inappreciable or lacking in Cw since female longevity was similar regardless of mating delay and also because post‐mating fecundity was roughly equivalent in the female groups mated until 20 days of age (MD0, MD10 and MD20).…”
Section: Discussionmentioning
confidence: 99%
“…Through oosorption, females are able to reallocate reproductive resources (mostly yolk material from mature oocytes) to fuel somatic maintenance, which would otherwise be wasted as unfertilised eggs. Thus, in response to a mating delay, females may allocate less resources to egg production and more to somatic maintenance, expecting future mating chances and reproduction (Alqurashi et al, 2023; Fadamiro & Baker, 1999; Proshold et al, 1982; Zheng et al, 2020). Our results, however, suggest that oosorption appears to be inappreciable or lacking in Cw since female longevity was similar regardless of mating delay and also because post‐mating fecundity was roughly equivalent in the female groups mated until 20 days of age (MD0, MD10 and MD20).…”
Section: Discussionmentioning
confidence: 99%
“…Adult Lucilia are anautogenous and require several protein meals to complete egg development, but even small protein meals can initiate yolk deposition in some eggs (Wall et al 2002, Alqurashi et al 2023). We observed that the ovaries of two-day-old flies reared (as larvae) on chicken meat had higher amounts of protein than those of flies reared on beef liver, and that this reflected the higher relative protein composition in the chicken meat itself.…”
Section: Discussionmentioning
confidence: 99%
“…Egg maturation in the related species L. sericata requires about a week if protein is provided (Wall et al 2002). Further research would be needed to determine whether the higher protein levels in eggs of young flies would be sufficient to speed up the timeline for egg maturation after the flies were given additional protein meals (Alqurashi et al 2023).…”
Section: Discussionmentioning
confidence: 99%